Infectious and Noninfectious Causes of Epiglottitis in Adults, Review of 24 Patients - Orhan, Israfil; Aydin, Salih; Karlidag, Turgut (Galenos Yayincilik, 2015)
Objective: The present study reports the etiological differences, clinical features, management, and patient outcomes between infectious and noninfectious causes of epiglottitis in adult patients. Methods: The medical records of 24 patients with infectious and noninfectious epiglottitis were investigated. Diagnosis was made by anamnesis and endoscopic examination. On admission, respiratory distress of patients was classified according to Freidman's classification. Results: Fifteen patients were male, and nine patients were female. Their ages ranged between 24 and 69 years of age (mean, 43.4 +/- 11.6). In total, 16 patients were diagnosed with infectious epiglottitis, and eight patients were diagnosed with noninfectious epiglottitis. Of patients with noninfectious epiglottitis, two had angioedema, two had experienced organophosphate ingestion, one had experienced hot water aspiration, one had experienced hot milk aspiration, one had experienced foreign body aspiration (fishbone), and one had epiglottitis due to Behcet's disease. Sore throat was the most common symptoms of infectious and noninfectious epiglottitis in our patients. Odynophagia was the second most common symptom of infectious epiglottitis, and muffled voice was the second most common symptom in noninfectious patients. Conclusion: Epiglottit is an emergency situation; when a patient is diagnosed with epiglottitis, close follow-up should be performed, and airway support should properly be maintained according to the degree of respiratory distress. Tracheostomy should be performed without hesitation, as needed.
Keywords: Epiglottitis; adult; etiology; diagnosis